School as an integrator: secondary’s studies in Navarra / La escuela como elemento integrador: estudio de la ESO en Navarra - Neus Caparrós Civera; Esther Casares García (Barataria, 2014)
The article presented here reflects the work done in schools of secondary education in Navarre. The objective of the research was to analyze the phenomenon of immigration through the perception of the different actors involved in the process itself: students, teachers and other professionals. The methodology is qualitative, based on interviews in depth to chiefs of studies of centers school by a high index of presence of immigrant pupils and, and quantitative based in more than 800 surveys to the pupils of the above mentioned centers distributed in the Navarre geography. The results obtained in it will be considered to be an starting point of item for the design of future social policies, to improve the integration of the immigrant, especially during the adolescence and to break prejudices of the native ones towards the immigrants, of these towards the autochthonous ones, and also among the foreigners.